Crop water stress index for off-season greenhouse green peppers in Liaoning, China - Bo, Li; Tieliang, Wang; Jian, Sun (International Journal of Agricultural and Biological Engineering, 2014)
The crop water stress index (CWSI) is a complex instrument to effectively monitor the degree of water stress of crops and provides guidance for timely irrigation. In an experiment utilizing the CWSI with off-season green peppers planted in barrels in a greenhouse in Liaoning Province, Northeast China, this study monitors the sub-indexes--such as canopy temperature, environmental factors and yield--determines the changing law of each constituent, achieves an empirical model as well as a baseline formula for the canopy temperature of the peppers with a sufficient water supply, and verifies the rationality of the formula with corresponding experimental data. The results obtained by using the CWSI show that the optimal time to determine the water deficit for off-season green peppers is at noon, by measuring the diurnal variation in the peppers with different water supplies. There is a nonlinear relationship between the yield and the average CWSI at the prime fruit-bearing period; moreover, the optimal time to supply water for off-season green peppers comes when the average water stress index ranges between 0.2 and 0.4 during the prime fruiting stage, thereby ensuring a high yield.Keywords: crop water stress index, off-season green peppers in greenhouse, high yield, canopy temperature, irrigation, water deficitDOI: 10.3965/j.ijabe.20140703.004Citation: Li B, Wang T L, Sun J. Crop water stress index for off-season greenhouse green peppers in Liaoning, China. Int J Agric & Biol Eng, 2014; 7(3): 28－35.